2022
DOI: 10.1039/d2dt00063f
|View full text |Cite
|
Sign up to set email alerts
|

Rational construction of a triphenylphosphine-modified tetra-nuclear Cu(i) coordinated cluster for enhanced chemodynamic therapy

Abstract: A triphenylphosphine-modified tetra-nuclear Cu(I) coordinated cluster was constructed for enhanced Chemodynamic Therapy (CDT) by increasing the metal centers. After inside human bladder cancer (T24) cells, a larger number of copper...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Furthermore, other copper complexes, such as Cin-ODÀ Cu, a novel copper coordination compound designed by Zhaoguo Hong et al, demonstrated the ability to inhibit tumor growth in both in vitro and in vivo studies. [179] To intensify ROS production in CDT, they synthesized a tetra-nuclear Cu(I) coordinated cluster, [183] which exhibited enhanced anti-tumor abilities through CDT owing to its higher copper content. This promising result opens up possibilities to improve the curative effects of CDT.…”
Section: Copper Complexes In Chemodynamic Therapymentioning
confidence: 99%
“…Furthermore, other copper complexes, such as Cin-ODÀ Cu, a novel copper coordination compound designed by Zhaoguo Hong et al, demonstrated the ability to inhibit tumor growth in both in vitro and in vivo studies. [179] To intensify ROS production in CDT, they synthesized a tetra-nuclear Cu(I) coordinated cluster, [183] which exhibited enhanced anti-tumor abilities through CDT owing to its higher copper content. This promising result opens up possibilities to improve the curative effects of CDT.…”
Section: Copper Complexes In Chemodynamic Therapymentioning
confidence: 99%
“…9,10 Compared with the traditional homo-metallic CDT agents, hetero-metallic Fenton-like centers have attracted increasing attention due to their excellent conversion efficiency for hydrogen peroxide. [11][12][13][14][15][16][17][18] Recently, ferrocene moieties with excellent redox properties have proved to be suitable for the CDT treatment strategy. [19][20][21][22][23] For example, Dong et al prepared a covalent organic framework (COF)-based ferrocene (Fc) and glutathione peroxidase 4 (GP × 4) inhibitor loaded nano drug RSL3@COF-Fc to enhance • OH-induced cellular damage by CDT.…”
Section: Introductionmentioning
confidence: 99%